The vanishing endometrioma: the intriguing impact of pregnancy on small endometriotic ovarian cysts. (11th July 2013) - Benaglia, Laura; Somigliana, Edgardo; Calzolari, Luca; Busnelli, Andrea; Cardellicchio, Lucia; Ragni, Guido; Fedele, Luigi
Abstract: There is a general belief that pregnancy has a beneficial effect on endometriosis but evidence is scanty. Moreover, some recent warning reports documented progression-growth of ovarian endometriomas during pregnancy. To further elucidate this aspect, we set up a prospective cohort study. We recruited 24 women carrying endometriomas at the time of in vitro fertilization who got pregnant. Selected women were contacted about 12–18 months after oocyte retrieval and invited to refer for ultrasound. The primary aim was to evaluate the modifications of endometriotic cysts after pregnancy. Twenty-four women carrying 40 endometriomas accepted to participate. The number of cysts per patient was significantly reduced following pregnancy ( p = 0.003). It was unchanged in eight cases (33%), increased in two cases (8%) and reduced in three cases (13%). In the remaining 11 women (46%), no cyst could be detected. A comparison of the size of the endometrioma could be done in 21 cysts; the mean ± SD diameter before and after pregnancy was 20 ± 9 and 18 ± 7 mm, respectively ( p = 0.27). In conclusion, pregnancy has a beneficial effect on endometriomas. A consistent proportion of cysts becomes undetectable after delivery. Further studies are warranted to clarify the mechanisms determining the disappearance of these cysts.